Producer immunity towards the lantibiotic Pep5: identification of the immunity gene pepI and localization and functional analysis of its gene product. - Reis, M (1994)
The lantibiotic Pep5 is produced by Staphylococcus epidermidis 5. Pep5 production and producer immunity are associated with the 20-kb plasmid pED503. A 1.3-kb KpnI fragment of pED503, containing the Pep5 structural gene pepA, was subcloned into the Escherichia coli-Staphylococcus shuttle vector pCU1, and the recombinant plasmid pMR2 was transferred to the Pep5- and immunity-negative mutant S. epidermidis 5 Pep5- (devoid of pED503). This clone did not produce active Pep5 but showed the same degree of insensitivity towards Pep5 as did the wild-type strain. Sequencing of the 1.3-kb KpnI-fragment and analysis of mutants demonstrated the involvement of two genes in Pep5 immunity, the structural gene pepA itself and pepI, a short open reading frame upstream of pepA. To identify the 69-amino-acid pepI gene product, we constructed an E. coli maltose-binding protein-PepI fusion clone. The immunity peptide PepI was detected in the soluble and membrane fractions of the wild-type strain and the immune mutants (harboring the plasmids pMR2 and pMR11) by immunoblotting with anti-maltose-binding protein-PepI antiserum. Strains harboring either pepI without pepA or pepI with incomplete pepA were not immune and did not produce PepI. Washing the membrane with salts and EDTA reduced the amount of PepI in this fraction, and treatment with Triton X-100 almost completely removed the peptide. Furthermore, PepI was hydrolyzed by proteases added to osmotically stabilized protoplasts. This suggests that PepI is loosely attached to the outside of the cytoplasmic membrane. Proline uptake and efflux experiments with immune and nonimmune strains also indicated that PepI may act at the membrane site.